(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Identification of noise level and indication of its impact on residential barrier design in street edge The effect of noises toward human body not only disturb the hearing organs, it can also disturb other human body parts and in some cases may results in reduction of work’s efficiency. This study aims to assess the noise level in residential areas on the edge of the city of Yogyakarta highway and to find any indication of the impact on building design and barriers by homeowners to reduce noise. This research is quantitative associative. Data obtained from measurements and field observations. The results showed that the noise level in residential areas on the edge of the highway, class II street and local roads in the city of Yogyakarta did not meet the standard values of LTNI and LNP. The design of buildings and barriers as a noise reduction factors for the highway was found with a percentage of 100% on the Jalan Bung Tarjo segment, 85.7% on the Jalan Ki Penjawi segment, 20.83% on the Jalan Juminahan segment, 52.08% on the Jalan Bausasran segment, 13.37% on the Jalan Suryodiningratan segment, and 10.7% on the Jalan Mangkuyudan segment. Therefore, the people of Yogyakarta are not fully aware of the high level of road noise.